STUDENTS’ RESPONSES TO THE IMPLEMENTATION OF GUIDED INQUIRY MODEL INTEGRATED WITH VOLCANIC DISASTER MITIGATION ON PHYSICS LEARNING - ANGGIE FERINA, YOELANDA (Inovasi Pendidikan Fisika, 2020)
This study aims to determine students responses to the implementation of physics learning with a guided inquiry model integrated with volcanic disaster mitigation. This type of research is quantitative descriptive research methods with quasi experimental design and research design Non-equivalent control group design. The subjects of this study were students of class XI odd semester 2019/2020 SMAN 1 Puncu Kediri which is a disaster-prone school under the foot of Mount Kelud. Student responses were collected using a response questionnaire that was prepared with a Likert scale and the results were analyzed descriptively quantitative. Based on data analysis, the results show that students responses to the implementation of physics learning with guided inquiry models integrated with volcanic disaster mitigation are included in the excellent category with an average percentage above 80% which shows that the model can be well received by students and can be applied further on learning physics and other subjects.Keywords: Guided Inquiry, Student?s responses, Disaster mitigation